While clearing the forests: The social-ecological memory of trees in the Anthropocene - Ibarra, Jose Tomas; Riquelme-Maulen, Wladimir; Banales-Seguel, Camila; Orrego, Gabriel; Salazar, Gonzalo (My University, 2024)
The Anthropocene concept raises awareness of human-induced planetary changes but is criticized for being 'too global'. We examined the social-ecological memory that emerges from people-tree relationships in South American temperate territories, Chile. We integrated dendrochronology (analysis of tree rings of 35 memorial trees; 17 species) with dendrography (participant observation complemented with semi-structured and go-along interviews with 14 interviewees; six women, eight men). We found that assemblages of people-tree relationships reflect marked historical changes in the territory, associated with the historical clearing of forests, which may be imprinted in both tree growth rings and in the social meanings and practices associated with memorial trees. In devastated territories, practices of tree care emphasize interconnectedness, multispecies collaborations, and the blurring of boundaries between humans and other-than-humans. We discuss some of the interdisciplinary and relational insights of our study, which may prove valuable for future research, political agendas, and educational programs in South America and beyond.
Keywords: chile; chthulucene; complex adaptive systems; habitat legacy; oral histories; temperate forests